Hepatitis C virus glycoprotein E2 binding to CD81: the role of E1E2 cleavage and protein glycosylation in bioactivity. - Chan-Fook, C; Jiang, W; Clarke, B; Zitzmann, N; Maidens, C; McKeating, J; Jones, I (Elsevier, 2000)
The hepatitis C virus glycoproteins E1 and 2 have been expressed using recombinant baculoviruses following fusion to the carrier protein glutathione S-transferase (GST). Proteins were expressed singly and as an E1E2 polyprotein with and without an N-terminal affinity tag. Expression of the E1E2 polyprotein, even when preceded by GST, led to processing in insect cells and detection of an E1E2 complex that could be specifically purified by glutathione affinity chromatography. Baculovirus expressed E2 and a purified GST-E1E2 protein bound to the second extracellular loop of CD81 (EC2), a reported ligand for the molecule, but not to a truncated derivative of CD81 consisting of only the central domain of the loop. Purified GST-E2, however, failed to bind to CD81 suggesting a requirement for a free E2 amino terminus for biological activity. The binding to CD81 by baculovirus expressed E2 protein was comparable to that observed for E2 derived from mammalian cells when detected by a monoclonal antibody sensitive to protein conformation. Furthermore, E2 protein expressed in insect cells in the presence of N-butyldeoxynojirimycin, an inhibitor of terminal glucose residue processing, formed complexes with E1 and bound to CD81-EC2 similarly to untreated protein. Together these data suggest that although hyperglucosylation of E2 does not have a major effect on bioactivity, polyprotein processing to reveal the free amino terminus is required.